Detecting fraud of financial statement through pentagon's fraud theory - Ali Murtado; Achmad Andru; Agustina Darmayanti; Krisno Adriadi (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2022)
This study aims to detect fraudulent financial statements using the Pentagon's fraud theory. The fraud pentagon theory is projected with financial targets, financial stabilities, external pressure, institutional ownership, ineffective monitoring, quality external auditors, change in auditor, capability, and CEO arrogancy. This study uses a quantitative research design and secondary data from 44 state-owned enterprises. The multiple regression analysis shows that external pressure and institutional ownership affect fraudulent financial statements. While financial targets, financial stabilities, ineffective monitoring, quality external auditors, change in auditor, capability, and arrogancy do not affect fraudulent financial statements.